2007
DOI: 10.2337/dc06-1755
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Psychosocial Factors and the Insulin Pump

Abstract: OBJECTIVE -The purpose of this study was to identify psychosocial issues related to diabetes, approaches to self-care, self-perceptions, and social interactions among insulin pump users with type 1 diabetes.RESEARCH DESIGN AND METHODS -Adult insulin pump users participated in focus groups loosely formed on the basis of A1C level. Transcripts of focus group meetings were coded into themes by five reviewers using NVivo2 qualitative software.RESULTS -Thirty adults with long-term diabetes participated in five focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(149 citation statements)
references
References 23 publications
(16 reference statements)
9
136
3
1
Order By: Relevance
“…The finding on body image concerns is similar to the results of our previous study on the insulin pump, where we found that participants' concerns about the insulin pump affected their body images, with an increased sense of self-consciousness in terms of clothing and public appearance [25]. Subjects in our study further expressed concern about the ways continuous glucose monitoring influenced their public appearance, and this affected their body and self images, particularly in intimate situations.…”
Section: Discussionsupporting
confidence: 80%
“…The finding on body image concerns is similar to the results of our previous study on the insulin pump, where we found that participants' concerns about the insulin pump affected their body images, with an increased sense of self-consciousness in terms of clothing and public appearance [25]. Subjects in our study further expressed concern about the ways continuous glucose monitoring influenced their public appearance, and this affected their body and self images, particularly in intimate situations.…”
Section: Discussionsupporting
confidence: 80%
“…In focus group interviews with 30 adults with T1D who were currently using insulin pumps, Ritholz and colleagues identified 4 major themes regarding respondents' reluctance to transition to insulin pump therapy. 8 These included the potential impact on diabetes self-care, emotional reactions to the insulin pump, body image, and social acceptance. Perceived complexity of insulin pumps, particularly among older patients, has also been suggested as a possible deterrent.…”
mentioning
confidence: 99%
“…33 Many studies report high levels of satisfaction amongst pump users and their caregivers particularly for the flexibility it confers. [34][35][36][37][38] Pump patients also report a more collaborative relationship with their health care professional (HCP), which in combination with the pump facilitates better diabetes control. 34 However, pumps can create additional work and obligations for families because of the potential to do frequent correction doses and set temporary basal rates.…”
Section: Pump Therapymentioning
confidence: 99%
“…Conversely patients with poor control tend to have more negative perceptions about pumps, take a passive approach, adhere poorly to pump selfmanagement tasks, and have unrealistic expectations of IPT leading to discouragement and frustration. 38 Pumps offer flexibility and the potential of a more normal lifestyle, but are a constant reminder of diabetes and could affect body image. Body image concerns are more pronounced in women, who report self-consciousness from wearing their pump and the inevitable questions that arise.…”
Section: -43mentioning
confidence: 99%